Genetic diversity of Nephtys hombergii (Phyllodocida, Polychaeta) associated with environmental factors in a highly fluctuating ecosystem. (16th January 2017) - Vasileiadou, Katerina; Pavloudi, Christina; Camisa, Federica; Tsikopoulou, Irene; Fragopoulou, Nina; Kotoulas, Georgios; Arvanitidis, Christos
Abstract : Genetic diversity and population distribution are influenced by environmental factors, yet information is scarce on the interrelations that define dispersal of populations. Transitional water ecosystems are hosting habitats with temporally and spatially variable conditions, which make them very useful in understanding the mechanisms affecting population establishment. For the study, seasonal samples were collected from four lagoons in the lagoonal complex of Amvrakikos Gulf (W Greece). The mitochondrial DNA (COI gene) was analysed from polychaetes of Nephtys hombergii, as it is considered an important component of these assemblages and shows great dispersal ability. The results of the genetic analysis showed intraspecific variability in all the lagoons, with genetic structuring tending to follow a seasonal pattern rather than a spatial one. The results of BIOENV analysis indicated correlation of the observed pattern with the water pH levels, the redox potential and the concentration of phosphate in the sediment. The complexity of the network suggested the enhancement of the local population with more recently established haplotypes. The findings of the study support the necessity of designing management strategies by taking into account genetic diversity and population demography approaches in addition to those based on species and habitats.